Measurement of polarization amplitudes and CP asymmetries in B0 → ϕ K[bar][ast](892)0 - Aaij, Roel; Aquines Gutiérrez, Osvaldo; Bachmann, Sebastian; Bien, Alexander; Blouw, Johan; Britsch, Markward; De Cian, Michel; Dordei, Francesca; Esen, Sevda; Färber, Christian; Fontana, Marianna; Gersabeck, Evelina; et al. (Journal of high energy physics, 2014)
An angular analysis of the decay B0 → ϕK*(892)0 is reported based on a pp collision data sample, corresponding to an integrated luminosity of 1.0 fb−1, collected at a centre-of-mass energy of $ \sqrt{s} $= 7 TeV with the LHCb detector. The P-wave amplitudes and phases are measured with a greater precision than by previous experiments, and confirm about equal amounts of longitudinal and transverse polarization. The S-wave K+π− and K+K− contributions are taken into account and found to be significant. A comparison of the B0 → ϕK*(892)0 and $ {{\overline{B}}^0}→ φ {{\overline{K}}^{*}}{{\left( {892} \right)}^0} $results shows no evidence for direct CP violation in the rate asymmetry, in the triple-product asymmetries or in the polarization amplitudes and phases.
The LHCb Collaboration: R. Aaij, O. Aquines Gutierrez, S. Bachmann, A. Bien, J. Blouw, M. Britsch, M. De Cian, F. Dordei, S. Esen, C. Färber, M. Fontana, E. Gersabeck, L. Grillo, X. Han, S. Hansmann-Menzemer, A. Jaeger, M. Kolpin, K. Kreplin, G. Krocker, B. Leverington, J. Marks, M. Meissner, M. Neuner, T. Nikodem, M. Schmelling, P. Seyfert, S. Stahl, U. Uwer, M. Vesterinen, S. Wandernoth, D. Wiedner, A. Zhelezov [und viele weitere]
Im Titel ist die Zahl "0" jeweils hochgestellt
Im Titel ist [ast] als Tropfensternchen (englisch: teardrop-spoked asterisk) dargestellt
Gesehen am 15.10.2020